Organic solvent stable lipase from Cryptococcus diffluens D44 isolated from petroleum sludge - SAYAR, NİHAT ALPAGU (ELSEVIER, 2015)
Microbial lipases, especially yeast lipases, are extensively used for biodiesel production. In order to reduce biodiesel production cost, development of stable enzymes under extreme conditions is one of the important prominences. To this end, the properties of a lipase of Cryptococcus diffluens D44, isolated from petroleum sludge, has been investigated. Crude extracellular D44 lipase showed maximal activity at pH 9.0 and 45 degrees C. Half-life of the enzyme at 30, 40, 50 and 60 degrees C was 79.67, 45.90, 39.16 and 2 min, respectively. Activation energy of p-nitrophenyl palmitate (pNPP) hydrolysis was 30.13 kJ mol(-1). 044 lipase was active within a broad range of pH from 6.0 to 10.0 with the optimum pH at 9.0. SDS-PAGE and MALDI-TOF fingerprint analyses revealed the molecular weight of the enzyme to be 45.7 kDa. Its inhibition with ethylenediaminetetraacetic acid (EDTA) indicated that D44 lipase requires metal ions as cofactors. Km and Vm values were 1.92 x 10(-4) mM (0.000073 mg/ml) pNPP and 96.15 U/min, respectively. Lipase activity was enhanced in the presence of Ca2+, Mg2+, K+ and Mn+, while Na+ and Ni+ has not altered enzyme activity. Methanol, tert-butyl alcohol, acetonitrile and ethanol resulted in an increase in percentage residual activity after 1 and 12 h of incubation. Highest residual activity, 276.43%, was obtained in 10% methanol following 12 h of incubation. The extensive stability of D44 lipase in aqueous methanol makes C. diffluens D44 lipase suitable for biodiesel production, since moderate reaction conditions and less organic solvent concentrations are required for oil based fuel production. This is the first report of the biochemical characterization of a lipase from C. diffluens. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cryptococcus diffluens; Lipase; Biodiesel; Gompertz; EXTRACELLULAR LIPASE; PURIFICATION